Diskrepansi Pembayaran BPJS Kesehatan Terhadap Klaim Pelayanan IGD Berdasarkan PERMENKES Nomor 27 Tahun 2014 - Johan, Willy; Yuyut Prayuti; Arman Lany (Magister Ilmu Hukum - Universitas Hang Tuah, 2024)
In realizing Universal Health Coverage (UHC), Indonesian government has launched a national health insurance program (JKN) organized by the Health Social Security Administering Agency (BPJS) starting from January 01, 2014. The policy of determining outpatient episodes for patients in the emergency department (ED) who receive treatment for less than 6 hours raises problems related to claims for services provided by service providers. Hospitals are required to provide health services in emergency situations to save lives and prevent disabilities, while also having profit objectives. This research aims to describe the output and impact in relation to the regulations. The research uses normative legal research methods with statute approach, conceptual approach and a non-judicial case study approach, presenting several cases related to discrepancies between ER services provided and claims paid, especially for patients who die in the ER within 6 hours, which is suspected to cause hospitals to be selective in handling emergency patients. The Minister of Health Regulation No. 27 of 2014 regarding INA-CBG creates dilemmas and challenges for hospitals in providing optimal services for emergency cases in the ER.